Assessing the Quality of Health Economic Evaluation Research by CHEERS Instrument: A Critical Literature Review in Laos, Cambodia, and Myanmar - Hoang Nam Nguyen, Ky Nhu Ly, Quang Trung Vo (Journal of Applied Pharmaceutical Science, 2017)
Although economic evaluations play vital roles in healthcare setting, omissions of these reports in Laos, Cambodia, and Myanmar make themselves not to be relied or trusted. Therefore, this study appraises deliberately the quality of inside information to decide which report can be used for assisting policy-makers. It was conducted in August 2016, using PubMed, Science Direct and Cochrane databases for searching economic analyses published from 1996 to 2016 with following terms either alone or in combination: economic evaluation, cost-effectiveness analysis, cost-benefit analysis, cost-minimization analysis, cost-utility analysis, Laos, Cambodia, Myanmar. Qualified articles are independently assessed by two reviewers based on Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist. 1285 articles citations were identified, but only 17 articles left after the selection. These articles are classified into four quality levels considered as good (n=4), fair (n=6), average (n=4) and below average (n=3). The mean percentage of recommendations fulfilled by papers is 71.3%. In brief, economic evaluations in these countries need to be increased in quantity as well as improved in quality. It is better to standardize by CHEERS guidelines and invest more funding supports for reports.
Keywords: Economic evaluation, quality assessment, systematic review, Cambodia, Laos, Myanmar.